Discovery of potent DOT1L inhibitors by AlphaLISA based High Throughput Screening assay. Issue 8 (1st May 2018) - Song, Yakai; Li, Linjuan; Chen, Yantao; Liu, Jingqiu; Xiao, Senhao; Lian, Fulin; Zhang, Naixia; Ding, Hong; Zhang, Yuanyuan; Chen, Kaixian; Jiang, Hualiang; Zhang, Chenhua; et al.
Graphical abstract: Through AlphaLISA assay, compound 3, which has been verified in vitro and ex vivo, was discovered as a novel DOT1L inhibitor. Abstract: DOT1L (the disruptor of telomeric silencing 1-like), through its methyltransferase activity of H3K79, plays essential roles in transcriptional regulation, cell cycle regulation, and DNA damage response. In addition, DOT1L is believed to be involved in the development of MLL-rearranged leukemia driven by the MLL (mixed-lineage leukemia) fusion proteins, which thus to be a crucial target for leukemia therapy. Hence, discovering of novel DOT1L inhibitors has been in a great demand. In this study, we initiated the discovering process from setting up the AlphaLISA based High Throughput Screening (HTS) assay of DOT1L. Combining with radioactive inhibition assay and Surface Plasmon Resonance (SPR) binding assay, we identified compound 3 and its active analogues as novel DOT1L inhibitors with IC50 values range from 7 μM to 20 μM in vitro . Together with the analysis of structure activity relationships (SAR) and binding modes of these compounds, we provided clues to assist in the future development of more potent DOT1L inhibitors. Moreover, compounds 3 and 9 effectively inhibited the proliferation of MLL-rearranged leukemia cells MV4-11, which could induce cell cycle arrest and apoptosis. In conclusion, we developed a HTS platform based on AlphaLISA method for screening and discovery of DOT1L novel inhibitor, through which we discovered compound 3 and its analogues as potent DOT1L inhibitors with promising MLL-rearranged leukemia therapeutic application.